Improving Students’ Vocabulary Mastery Through Flashcard Media at the Eighth Grade - Agustin, Milan Dwi (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2024)
The problem of this study was that the students’ vocabulary mastery was still low. The objective of the research was to find out whether flashcards could improve students’ vocabulary mastery at the eighth grade of Mts. Raudlatus Syabab. This study used Classroom Action Research (CAR) with a collaborative design. The participants were 26 students of class 8C. The research was carried out in two cycles, each consisting of planning, implementing, observing, and reflecting stages. The data collection techniques included a preliminary test and post-test, observation sheets, and interviews. Content validity was ensured by involving the English teacher, and the researcher administered two tests and determined the criteria of success. The minimum score set to achieve the criteria of success was 75, with at least 65% of students required to meet or exceed this score. The results showed that in cycle 2, students were still unable to pronounce words correctly and fluently, although their performance improved with different subject matter and treatment, reaching an average score of 73%. Therefore, it can be concluded that flashcard media can improve students’ vocabulary mastery.